Að hafa í sig og á. Isländsk fraseologi i ett isländskt-svenskt perspektiv - Hannesdóttir, Anna Helga; Jónsson, Jón Halmar (LexicoNordica, 2001)
In this paper we discuss a new approach to Icelandic phraseology in an Icelandic- Swedish dictionary. A finite set of semantic fields forms the structure on which the lexical description is based, and each field is further structured into subsets according to the diverse meanings of the phrases involved. A key feature of a dictionary of this kind is its multiple access structure, allowing access to the concepts, the key words of the phrases, and the phrases themselves. Each phrase is attached to one or more semantic field(s). Here we illustrate the method by the field FJÁRHAGUR, i.e. economy. The structure of the field is illustrated, the core vocabulary within the field is presented and defined, followed by phrases belonging to the field. Through the multiple access structure it is possible to register and describe lexical entities and concepts that have not been lexicalized as single words. Such entities are poorly treated in traditional, word-based dictionaries. The bilingual perspective on the parallel monolingual description of each of the languages is meant to add a genuine contrastive dimension to the lexical analysis. At a more principal level, this paper also deals with the advantages of this access structure compared to those of ordinary bilingual dictionaries. Some of the shortcomings of traditional bilingual lexicography in general are discussed, as well as some weaknesses characteristic of such lexicography as where two closely related languages are involved.